Memupuk Jiwa Pustakawan Sejak Dini: Refleksi Implementasi Literasi Informasi dalam Menciptakan Masyarakat Terinformasi - Alam, Umar Falahul (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2021)
Introduction. information literacy for all of the community is a condition that is predicted by the Indonesian government to be realized immediately. This achievement will create an informed society. This situation can be realized if the librarian's soul becomes the soul of the community. Therefore, two things that must be prepared are first, increasing interest in reading in the community, and second, carrying out an information literacy program.Methodology. This paper is library research. Writing analysis uses a qualitative descriptive method by capturing the fact. This study uses relevant literature to relate the research theme in formulating the problems that occur and in making final conclusions.Results and discussion. Librarians who are referred to as